Consumer and Health Care Professional Perspectives on a Digital Platform to Support Preventive Antenatal Care: Qualitative Descriptive Study - Emma Doherty; Sophie Dilworth; Alice Rice; Taya Wedesweiler; Ranju Shrestha; Sharni Greenwood; Michelle Foster; Janaya Lewis; Justine Daly; Rebecca Wyse; Carly Mallise; Melanie Kingsland (JMIR Formative Research, 2026)
Background Modifiable health risks in pregnancy are common and contribute to adverse maternal and infant outcomes, yet preventive care addressing these risks can be difficult to deliver within time-limited antenatal appointments. Hybrid models combining in-person care with digital platforms offer a promising solution; however, there is limited evidence regarding consumer and health care professional perspectives on the preferred content and functionality of such platforms to inform their design. Objective This study aimed to explore consumer and health care professional perspectives on the ideal content and functionality of a digital platform to support preventive antenatal care. Methods A descriptive qualitative study was conducted across 2 regional maternity services in New South Wales, Australia. Four workshops were held with recently pregnant consumers and antenatal health care professionals, using purposive sampling to include Aboriginal and culturally and linguistically diverse participants. Data were analyzed using applied thematic analysis, guided by a predefined framework, which examined what content should be included, how the platform should function, and why it was needed. Results A total of 23 consumers and 12 health care professionals participated. Participants identified key content requirements, including digital risk assessments, evidence-based and personalized information, practical resources, clear support options, and content extending into the postbirth period. Preferred functionalities included early access to the platform, appointment-aligned reminders, integration with routine workflows, tracking tools, multiple content delivery formats, filtering options, and information-sharing options. Participants described gaps in early pregnancy information and noted that digitally provided care could reduce stigma, support more honest disclosure, and enhance communication. Conclusions Consumers and health care professionals identified key content and functionality requirements for a digital platform to support preventive antenatal care. Prioritizing credible information, early access, and integration with routine workflows may improve the acceptability and utility of digital solutions. Future research is needed to examine real-world implementation.